E-Education : Social Media Network for Distance Learning System - Arnes Yuli Vandika; Eka Imama Novita Sari; Ade Kurniawan; Ruri Koesliandana (International Conference on Education and Language (ICEL), 2014)
E-Education using for setting of pedagogic practices with emphasis on learning with the use of electronic instruments. Education by itself changes fundamentally where electronics are at stake; it is will have a different character and a different understanding of the social relations that sustain the process of education. E-education embodies furthermore specific programs and devices, which are not only confined to information (data transference and e-learning), amusement (e-games) or storytelling (like what happens in family circles). Goals beyond them are generally described in vague terms such as personal growth or change. Social Media Network is change is indeed the key notion in the case of e-education. Any form of change achieved in knowledge, behavior or attitude can be tested in e-education through accessing the student's feedback, which is registered in connected computer programs